Peran Struktur Kalimat Efektif dalam Memahami Isi UUD 1945 - Dali, Meilina Widya; Abdullah, Adhi Pramana; Lambogo, Chaira R.; Abay, Arif Rahman; Bingo, Nur Arini A.; Hasan, Suleman; Abdjul, Faradila; Nusa, Lailandri; Habibie, Mochamad Panji Prasetya; Ibrahim, Rahmawati; Thalib, Randy; Kasim, Rilyo Rafly; Rajak, Sri Selviayani; Tolindu, Alya Ramadhani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study discusses the use of effective sentence structure in the text of the 1945 Constitution of the Republic of Indonesia and its influence on the understanding of norms. The study was conducted using a descriptive qualitative approach through a documentary study of several articles of the 1945 Constitution that have long and complex sentence structures. The analysis focused on syntactic elements and sentence effectiveness based on the principles of clarity, unity of meaning, and language efficiency. The result of the study indicates that sentences that are structured simply and clearly are easier to understand than compound sentences that are layered and long, although they still contain complete normative meaning. Effective sentence structure helps reduce norm ambiguity, increases legal certainty, and makes it easier for the public, academics, and students to understand the contents of the 1945 Constitution. Therefore, improving the quality of sentence structure in the text of the 1945 Constitution is important so that norms can be understood more clearly and are accessible to all levels of society.